Prognostic value of right ventricular dilatation on computed tomography pulmonary angiogram for predicting adverse clinical events in severe COVID-19 pneumonia - Beyls, Christophe; Vial, Jeremie; Lefebvre, Thomas; Muller, Charlotte; Hanquiez, Thomas; Besserve, Patricia; Guilbart, Mathieu; Haye, Guillaume; Bernasinski, Michael; Huette, Pierre; Dupont, Hervé; Abou-Arab, Osama; et al. (Frontiers in Medicine, 2023)
Background Right ventricle dilatation (RVD) is a common complication of non-intubated COVID-19 pneumonia caused by pro-thrombotic pneumonitis, intra-pulmonary shunting, and pulmonary vascular dysfunction. In several pulmonary diseases, RVD is routinely measured on computed tomography pulmonary angiogram (CTPA) by the right ventricle-to-left ventricle (LV) diameter ratio > 1 for predicting adverse events. Objective The aim of the study was to evaluate the association between RVD and the occurrence of adverse events in a cohort of critically ill non-intubated COVID-19 patients. Methods Between February 2020 and February 2022, non-intubated patients admitted to the Amiens University Hospital intensive care unit for COVID-19 pneumonia with CTPA performed within 48 h of admission were included. RVD was defined by an RV/LV diameter ratio greater than one measured on CTPA. The primary outcome was the occurrence of an adverse event (renal replacement therapy, extracorporeal membrane oxygenation, 30-day mortality after ICU admission). Results Among 181 patients, 62% (n = 112/181) presented RVD. The RV/LV ratio was 1.10 [1.05–1.18] in the RVD group and 0.88 [0.84–0.96] in the non-RVD group (p = 0.001). Adverse clinical events were 30% and identical in the two groups (p = 0.73). In Receiving operative curves (ROC) analysis, the RV/LV ratio measurement failed to identify patients with adverse events. On multivariable Cox analysis, RVD was not associated with adverse events to the contrary to chest tomography severity score > 10 (hazards ratio = 1.70, 95% CI [1.03–2.94]; p = 0.04) and cardiovascular component (> 2) of the SOFA score (HR = 2.93, 95% CI [1.44–5.95], p = 0.003). Conclusion Right ventricle (RV) dilatation assessed by RV/LV ratio was a common CTPA finding in non-intubated critical patients with COVID-19 pneumonia and was not associated with the occurrence of clinical adverse events.